The Effect Fears of Missing Out (Fomo) on Women Muslims Consumer - Rezi Muhamad Taufik Permana; Eka Tresna Gumelar; Nindya Saraswati (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The phenomenon of fear of missing out (FoMO) among the current generation Z has become a quite unique phenomenon from the perspective of consumer behavior. The FoMO phenomenon of cosmetic products is very interesting to see what factors can influence this. the emergence of FoMO behavior that has an impact on consumer behavior. This study uses a quantitative approach with non-probability sampling techniques because researchers do not know for sure the actual number of the study population. Purposive sampling was used in sampling in this research where respondent criteria were required to achieve the objectives of this research. Meanwhile, data analysis on this research uses structural equation modeling with SmartPLS software. The results show that the factors that influence FoMO arise significantly from the influence of Influencer Marketing and Social Media Marketing, where FoMO has a positive effect on changes in consumer behavior